Bacterial biota of Nigeen Lake waters (Kashmir Valley). (August 2016) - Zaffar, Riasa M.; Ganai, Bashir A.
Abstract: One of the greatest apprehensions of water consumers all over the world with respect to the quality of drinking water is its contamination with pathogenic microorganisms. This research work determined the potential bacterial contaminants of the waters of Nigeen Lake, a subsidiary of Dal Lake and is regarded as a separate lake in Kashmir. The study was carried out from May 2014 to November 2014 excluding August and September at four different sites. During the study the bacterial flora showed variation in relation to the conditions prevailing at different sites. The highest viable count of bacteria was observed at Site:2 (surrounded by residential hamlets) followed by Site:1 (inlet) and Site:4 (centre) followed by Site:3 (outlet). Based on the examination of morphological features of bacterial colonies on nutrient agar plates after 48 h of incubation period, 40 different strains were isolated. The isolates were identified with the help of Gram's staining and DNA sequencing, 55% of the strains were Gram negative and 45% of the strains were Gram positive. With the help of 16S rRNA sequencing, out of the 40 isolates of bacteria, 7 strains were different at the genetic level. The bacteria which were identified with the help of DNA sequencing are Pseudomonas synxantha, Delftia acidovorans, Bacillus pumilus, Bacillus licheniformis, Macrococcus caseolyticus, Azotobacter vinelandii, and Stenotrophomonas maltophiria . Highlights: Bacterial biota of Nigeen Lake waters (Kashmir Valley) was carried out. Bacterial isolates were identified by Gram staining, DNA and rRNA sequencing. Identified bacteria were both Gram-positive as well as Gram-negative.